Magnesium Supplementation in Chronic Diseases - Sylwia Lach; Kinga Kałuża; Ilona Bednarek; Aleksandra Kowalczyk; Adrian Pączek; Paweł Dyczek; Julia Hofman; Wiktoria Staniszewska; Aleksandra Mucha; Olaf Jadanowski (Archiv Euromedica, 2026)
Europäische Wissenschaftliche Gesellschaft Home About the Journal Peer Review Editorial Board For Authors Reviewer Recognition Archive Contact Impressum EWG e.V. Elektronische Zeitschriftbibliotek Logo Bielefeld Academic Search Engine Logo Erfolgreich durch internationale Zusammenarbeit Metabolism endocrinology and obesity Cite as: Archiv EuroMedica. 2026. 16; 1. DOI 10.35630/2026/16/Iss.1.006 Received 20 November 2025; Accepted 9 February 2026; Published 14 February 2026 Magnesium Supplementation in Chronic Diseases Sylwia Lach1 email orcid id logo, Kinga Kałuża2 orcid id logo, Ilona Bednarek2 orcid id logo, Aleksandra Kowalczyk3 orcid id logo, Adrian Pączek4 orcid id logo, Paweł Dyczek5 orcid id logo, Julia Hofman3 orcid id logo, Wiktoria Staniszewska5 orcid id logo, Aleksandra Mucha3 orcid id logo, Olaf Jadanowski6 orcid id logo 1Independent Public Health Care Institution of the Ministry of Internal Affairs and Administration in Kielce, Poland 2Provincial Specialist Hospital in Czerwona Góra, Chęciny, Poland 3Medical University of Silesia in Katowice, Poland 4Zagłębiowski Clinical Hospital in Czeladź, Poland 5Wojewódzki Hospital in Bielsko-Biała, Poland 6University of Health Sciences in Bydgoszcz, Poland download article (pdf) lachsylwia@interia.eu ABSTRACT Background Magnesium is an essential intracellular cation involved in enzymatic reactions, energy metabolism, neuromuscular transmission, and cardiovascular regulation. Hypomagnesemia is common in patients with chronic diseases, particularly type 2 diabetes, metabolic syndrome, cardiovascular disorders, and neuropsychiatric conditions, and is frequently underrecognized in clinical practice. Aims The aim of this narrative review is to systematize current clinical and experimental evidence on the role of magnesium deficiency and the effects of magnesium supplementation in chronic diseases, with particular attention to metabolic, cardiovascular, and neuropsychiatric outcomes, as well as drug associated hypomagnesemia. Methods A narrative review was performed based on analysis of 46 English language publications retrieved from PubMed and Google Scholar and published between 2020 and 2025. The included studies addressed magnesium homeostasis, causes of hypomagnesemia, and clinical or molecular effects of magnesium supplementation in chronic diseases. No quantitative meta analysis or formal quality assessment was conducted. Results The reviewed evidence indicates that magnesium deficiency is associated with insulin resistance, endothelial dysfunction, inflammatory activation, and neuropsychological disturbances. Magnesium supplementation is associated with modest improvements in intermediate clinical parameters, including glycemic control, blood pressure, inflammatory markers, lipid profile, sleep quality, mood, and selected neuropsychological outcomes, particularly in individuals with low baseline magnesium status. Most available data relate to surrogate endpoints rather than hard clinical outcomes. Conclusions Magnesium deficiency is common in chronic diseases and may contribute to metabolic, cardiovascular, and neuropsychiatric dysregulation. Current evidence supports consideration of magnesium assessment and supplementation in selected high risk populations as an adjunctive measure. Further well-designed clinical studies are required to define optimal dosing strategies, duration of supplementation, formulation specific effects, and clinically meaningful long-term outcomes.